Bioengineering bone tissue with 3D printed scaffolds in the presence of oligostilbenes - Posa, Francesca; Di Benedetto, Adriana; Ravagnan, Giampietro; Cavalcanti-Adam, Elisabetta A.; Lo Muzio, Lorenzo; Percoco, Gianluca; Mori, Giorgio (Materials, 2020)
Diseases determining bone tissue loss have a high impact on people of any age. Bone healing can be improved using a therapeutic approach based on tissue engineering. Scientific research is demonstrating that among bone regeneration techniques, interesting results, in filling of bone lesions and dehiscence have been obtained using adult mesenchymal stem cells (MSCs) integrated with biocompatible scaffolds. The geometry of the scaffold has critical effects on cell adhesion, proliferation and differentiation. Many cytokines and compounds have been demonstrated to be effective in promoting MSCs osteogenic differentiation. Oligostilbenes, such as Resveratrol (Res) and Polydatin (Pol), can increase MSCs osteoblastic features. 3D printing is an excellent technique to create scaffolds customized for the lesion and thus optimized for the patient. In this work we analyze osteoblastic features of adult MSCs integrated with 3D-printed polycarbonate scaffolds differentiated in the presence of oligostilbenes.
Gesehen am 26.11.2020